2020
DOI: 10.1093/brain/awaa138
|View full text |Cite
|
Sign up to set email alerts
|

The role of the inferior parietal lobule in writer’s cramp

Abstract: Humans have a distinguishing ability for fine motor control that is subserved by a highly evolved cortico-motor neuronal network. The acquisition of a particular motor skill involves a long series of practice movements, trial and error, adjustment and refinement. At the cortical level, this acquisition begins in the parieto-temporal sensory regions and is subsequently consolidated and stratified in the premotor-motor cortex. Task-specific dystonia can be viewed as a corruption or loss of motor control confined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…In our TSD sample, structural alterations in cortical regions may be attributed to abnormal plastic remodeling processes or to primary pathophysiological processes, independent of the overuse that is typical of musician's dystonia but not of writer's cramp and spasmodic dysphonia 17,19,20 . Previous MRI studies suggested the presence of altered brain function (disrupted cortical representation, inhibitory function, and functional connectivity) in both musician's and non‐musician's TSD, which together with morphometric GM changes might be interpreted as consequences of maladaptive neuronal plasticity or as specific traits of the disease 2,8,17,21‐25 . Future combined functional/structural longitudinal MRI studies might at least partially disentangle this issue.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our TSD sample, structural alterations in cortical regions may be attributed to abnormal plastic remodeling processes or to primary pathophysiological processes, independent of the overuse that is typical of musician's dystonia but not of writer's cramp and spasmodic dysphonia 17,19,20 . Previous MRI studies suggested the presence of altered brain function (disrupted cortical representation, inhibitory function, and functional connectivity) in both musician's and non‐musician's TSD, which together with morphometric GM changes might be interpreted as consequences of maladaptive neuronal plasticity or as specific traits of the disease 2,8,17,21‐25 . Future combined functional/structural longitudinal MRI studies might at least partially disentangle this issue.…”
Section: Discussionmentioning
confidence: 76%
“…17,19,20 Previous MRI studies suggested the presence of altered brain function (disrupted cortical representation, inhibitory function, and functional connectivity) in both musician's and non-musician's TSD, which together with morphometric GM changes might be interpreted as consequences of maladaptive neuronal plasticity or as specific traits of the disease. 2,8,17,[21][22][23][24][25] Future combined functional/structural longitudinal MRI studies might at least partially disentangle this issue.…”
Section: Cortical Alterationsmentioning
confidence: 99%
“…Different forms of dystonia have been characterized by similarities in largescale disorganization of gray and white matter architecture, including abnormal distribution of influential regions of information transfer (hubs) in prefrontal, parietal, occipital cortices and thalamus and reduced connectivity of the sensorimotor and frontoparietal regions (19)(20)(21)(22)(23). This knowledge critically shifted our understanding of dystonia pathophysiology from a basal ganglia disorder to a largescale neural network disorder and thrust the field toward probing these alterations as potential candidate markers for its diagnosis and treatment (24)(25)(26)(27)(28).…”
Section: Significancementioning
confidence: 99%
“…The dorsal part of the IPL (dIPL) is a multimodal sensory association region involved in the initial acquisition and learning of a motor task. The anterior parts of the IPL, PMv, and M1 consist of the ne motor control network [54][55][56][57] . The dorsal premotor cortex (PMd) is involved in movement selection 58 .…”
Section: Discussionmentioning
confidence: 99%